Students’ perception towards using electronic feedback after the pandemic: Post-acceptance study - Al-Maroof, Rana Saeed; Alnazzawi, Noha; Akour, Iman; Ayoubi, Kevin; Alhumaid, Khadija; Nasser, Nafla Mahdi; Alaraimi, Samira; Al-Bulushi, Asma Ali; Thabit, Sarah; Alfaisal, Raghad; Aburayy, Ahmad; Salloum, Said (International journal of data and network science (Print), 2022)
Recent studies on e-feedback have answered many questions concerning the effectiveness of e-feedback in educational and non-educational sectors. They stated clearly that e-feedback is efficient and practical. From both teachers’ and students’ perspectives, e-feedback has influenced their learning and teaching environment effectively. It is a good technique to personalize the learning strategies. Based on the previous assumption, this study aims at exploring the effectiveness of e-feedback in an educational environment taking into consideration the TAM model and the external factors of trustworthiness and enjoyment. The data is collected by an online questionnaire that was distributed among a group of students. Facilitating communication among teachers and students. It helps in replacing the traditional feedback and assess the learning environment during the pandemic periods. The two constructs of perceived ease of use and perceived usefulness affect positively the intention to use the e-feedback and initiates this type of feedback as a prominent procedure to be used frequently in the learning environment. In addition, the perceived enjoyment and perceived trustworthiness increase the chance of using e-feedback. Recently, e-feedback is highly dominant among online platform users.